Tantangan Dan Peluang Manajemen Sumber Daya Manusia Pascapandemi - Tintin Tiwadaningsih; Banuara Nadeak; Solehudin Solehudin (Journal of Economic, Bussines and Accounting (COSTING), 2022)
After the outbreak of COVID-19, digitization was raised to a new level of importance. Since the beginning of the pandemic, human resource managers have faced various difficulties and obstacles. After the pandemic, human resource management may be faced with new problems, as well as new patterns in the workplace as a result of the outbreak. These difficulties are discussed in more detail in the second part of this study. The author of this article looks at the perspectives of business executives and experts from around the world on the future of work in this article. They emphasized the importance of developing organizational culture, enhancing people's competence, and encouraging the integrity of more sensitive individuals to deal effectively and efficiently with the post-pandemic transition after the outbreak. Thus, a systemic and procedural approach will require new strategies for leadership, staff engagement, and the formation of a post-pandemic customer-centric attitude. The physical and mental recovery of society in the post-pandemic era is about trust, respect, solidarity and most important human values. Keywords : COVID-19 Pandemic, Post-pandemic, Challenges and Opportunities, Human Resource Management